AKTIVITAS LARVASIDA EKSTRAK ETANOL, FRAKSI N-HEKSAN, ETIL ASETAT, DAN METANOL DAUN SEMBUKAN TERHADAP LARVA NYAMUK Aedes aegypti DAN ANOPHELES INSTAR III - Rollando Rollando; Maywan Hariono (Majalah Obat Tradisional, 2016)
Stinkvine (Paederia foetida L.) is known as a plant that has many properties that are empirically used in traditional medicine. However, information of utilization of Stinkvine leaf outside as a traditional medicine has not been discovered yet. This research aims to determine the potential larvicidal extracts and fractions of stinkvine leaf. The ethanol extract of stinkvine leaf fractionated using column chromatography with n-hexane, ethyl acetate, and methanol. Larvicidal activity test against Aedes aegypti and Anopheles III instar was done using 25 larvae for each treatment extracts and fractions in 5 series of concentration, and left exposed for 24 hours. Total mortality of larvae is calculated and analyzed using a modified Finney probit to determine the LC50 and LC90 values. The results showed larvicidal activity on larvae of Aedes aegypti mosquitoes with LC50 and LC90 value of n-hexane, ethyl acetate, and methanol fraction respectively 67,89 ; 10,92 ; 30,98 µg/mL and 114,11 ; 18,80 ; 54, 12 µg/mL. Larvicidal activity on larvae of Anopheles mosquitoes with LC50 and LC90 value of n-hexane, ethyl acetate, and methanol fraction respectively 50,76 ; 14,96 ; 60,82 µg/mL and 87,23 ; 25,65 ; 90,92 µg/mL. Ethyl acetate fraction of ethanol extract of stinkvine leaf (Paederia foetida L.) shows to have highest larvicidal activity against the mosquito larvae of Aedes aegypti and Anopheles. The results of GC-MS analysis of the ethyl acetate fraction showed there are 15 compounds, a constituent component consisting of lupeol (20,32 %), gamma-sitosterol (12,22 %), cyclohexanecarboxamide (11,82 %), campesterol (11,45 %), 3-butenol, 4- (2,6,6-trimethyl-1-sikloheksenil) (7,98 %), siklolanos-24-en-3-ol (7,87%), and there are 9 other components with a percentage amount of 0,18 to 5,86 %.